Towards a plurilingual and intercultural perspective in foreign language education for indigenous students in a university context - Arismendi Gómez, Fabio Alberto (2023)
In this article, we discuss the implications of having indigenous students in training programs at a university level. The discussion arises from the findings of a case study conducted in the undergraduate program on foreign language teaching (English and French), in a Colombian university. Eight indigenous students coming from different ancestral communities participated in this study. Data come mainly from individual and collective interviews conducted with the students as well as focus groups conducted with their teachers. Findings suggest implications in three domains: at an institutional level, at a pedagogical and methodologicallevel, and for the students themselves. A plurilingual and intercultural perspective can illuminate the different actions that could be implemented in each of these domains, in order to contribute to a fairer and more equitable foreign language education.